Réponses

2013-03-08T17:05:35+01:00

a(x) = x² - 9

= x² - 3²

= (x+3)(x-3)

 

b(x) = 4x² - 5

= (2x+√5)(2x-√5)

 

c(x) = 16x² - 49

= (4x+7)(4x-7)

 

d(x) = x² + 8x + 16

= (x+4)²

 

e(x) = 4x² -12x +9

= (2x+3)²

 

f(x) = 9-(2-x)²

= 3² - (2-x)²

= [3 + (2-x)][3 - (2-x)]

= (3 +2 -x)(3 -2 +x)

= (5 - x)(1 + x)

 

g(x) = (6x-1)² -4x²

= [(6x-1) + 2x][(6x-1) - 2x]

= (6x -1 +2x)(6x -1 -2x)

= (8x - 1)(4x -1)

 

h(x) = 49x² - (3x-4)²

= [7x + (3x-4)][7x - (3x-4)]

= (7x +3x -4)(7x -3x +4)

= (10x - 4)(4x + 4)

 

Voilà ;)

2013-03-08T17:08:35+01:00

a)  x²-9

    x²-3²

   (x-3)(x+3)

b) 4x²-5

     (2x-racine de 5)(2x+racine de 5)

c) 16x²-49

    (4x)²-7²

(4x-7)(4x+7)

d) x²+8x+16

     x²+2fois xfois 4+4²

    (x+4)²

e)4x²-12x+9

(2x)²-2fois2xfois3+3²

(2x-3)²